2007
DOI: 10.1080/14756360701228491
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of novel N–H and N-substituted indole-2- and 3-carboxamide derivatives as antioxidants agents

Abstract: We have previously reported on the synthesis of novel indole derivatives where some compounds showed significant antioxidant activity. Here, we report the synthesis of novel NZH and N-substituted indole-2-and 3-carboxamide derivatives and investigated their antioxidant role in order to identify structural characteristics responsible for activity. Although all compounds showed a strong inhibitory (95 -100%) effect on superoxide anion (SOD) only compounds 4, 5 and 6 showed simliar potency for the inhibition of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…IR spectra were recorded on KBr discs, using a Perkin-Elmer Model 1600 FT-IR spectrometer. 1 H NMR and HSQC spectra were obtained on Varian UNITY INOVA 500 spectrophotometers using DMSO-d 6 . Mass spectra were determined on an AGILENT 1100 MSD instrument.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IR spectra were recorded on KBr discs, using a Perkin-Elmer Model 1600 FT-IR spectrometer. 1 H NMR and HSQC spectra were obtained on Varian UNITY INOVA 500 spectrophotometers using DMSO-d 6 . Mass spectra were determined on an AGILENT 1100 MSD instrument.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that the examined indoline derivatives had effective activities as radical scavengers [5]. Some indole-3-carboxamides were potent inhibitors of superoxide anion formation [6,7]. Several benzimidazole containing indole derivatives showed very good in vitro free-radical scavenging properties as shown by determination of their scavenge superoxide anion formation capacity [8].…”
Section: Introductionmentioning
confidence: 97%
“…N-H and N-substituted indole-2-and 3-carboxamide showed a strong inhibitory (95-100%) effect on superoxide anion (SOD). Substitution on 1-position of the indole ring caused significant differences between the activity results regarding lipid peroxidation inhibition [42] emphasizing the differences in effects due to the derivative structure. …”
Section: Effect On Eggsmentioning
confidence: 99%
“…Several antioxidant pyrimidodiindole and pyridoindole derivatives were studied as melatonin receptor antagonists 18,19 . Recent data from our laboratory showed important antioxidant effects of N-substituted amide [20][21][22][23][24] and ester 25 derivatives of indole. Another study demonstrated that a series of 3-(substituted-benzylidene)-1,3-dihydro indolin-2 one and thione derivatives are effective as radical scavengers 26 .…”
Section: Research Articlementioning
confidence: 99%